Sputum‐to‐serum hydrogen sulphide ratio as a novel biomarker of predicting future risks of asthma exacerbation. Issue 9 (6th June 2018) - Suzuki, Y.; Saito, J.; Kikuchi, M.; Uematsu, M.; Fukuhara, A.; Sato, S.; Munakata, M.
Summary: Background: Increased level of hydrogen sulphide (H2 S) in sputum is reported to be a new biomarker of neutrophilic airway inflammation in chronic airway disorders. However, the relationship between H2 S and disease activity remains unclear. Objective: We investigated whether H2 S levels could vary during different conditions in asthma. Method: H2 S levels in sputum and serum were measured using a sulphide‐sensitive electrode in 47 stable asthmatic subjects (S‐BA), 21 uncontrolled asthmatic subjects (UC‐BA), 26 asthmatic subjects with acute exacerbation (AE‐BA) and 15 healthy subjects. Of these, H2 S levels during stable, as well as exacerbation states, were obtained in 13 asthmatic subjects. Results: Sputum H2 S levels were significantly higher in the AE‐BA subjects compared to the UC‐BA and healthy subjects ( P  < .05). However, serum H2 S levels in the AE‐BA subjects were lower than in the S‐BA subjects ( P  < .001) and similar to those in healthy subjects. Thus, the sputum‐to‐serum ratio of H2 S (H2 S ratio) in the AE‐BA subjects was significantly higher than in the S‐BA, UC‐BA and healthy subjects ( P  < .05). Among all subjects, sputum H2 S levels showed a trend to decrease with FEV1 %predicted and significantly positive correlations with sputum neutrophils (%), sputum IL‐8 and serum IL‐8. A multiple linear regression analysis showed that sputum H2 S was independently associated with increased sputum neutrophils (%) and decreased FEV1 %predicted ( P  < .05). The cut‐off level of H2 S ratio to indicate an exacerbation was ≥0.34 (area under the curve; 0.88, with a sensitivity of 81.8% and specificity of 72.7%, P  < .001). Furthermore, half of the asthmatic subjects with H2 S ratios higher than the cut‐off level experienced asthma exacerbations over the following 3 months after enrolment. Conclusions: The H2 S ratio may provide useful information on predicting future risks of asthma exacerbation, as well as on obstructive neutrophilic airway inflammation as one of the non‐Th2 biomarkers, in asthma.